Playing Identities, Performing Heritage: Meetings through Theatre - COPIL, Lorena (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
Theatrical Event: This Home is not for sale, Faculty of Theatre and Television, Babeș-Bolyai University Cluj-Napoca, in the European Project 2014-2860, Creative Europe, Playing Identities, Performing Heritage.